2017
DOI: 10.1371/journal.pone.0180271
|View full text |Cite|
|
Sign up to set email alerts
|

The prognostic and clinicopathologic characteristics of CD147 and esophagus cancer: A meta-analysis

Abstract: ObjectiveThe prognostic significance of CD147 expression in esophageal cancer patients remains controversial. Using a meta-analysis, we investigated the prognostic and clinicopathologic characteristics of CD147 in esophageal cancer.MethodsA comprehensive literature search of the PubMed (1966–2016), EMBASE (1980–2016), Cochrane Library (1996–2016), Web of Science (1945–2016), China National Knowledge Infrastructure (1982–2016), and Wanfang databases (1988–2016) was performed to identify studies of all esophagea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 20 publications
2
15
0
Order By: Relevance
“…In our study, the proportion of PMA ranged from 2.92% to 4.65%, a result consistent with findings from previous studies indicating that PMA composes 2%‐10% of lung adenocarcinoma patients . Female patients accounted for the majority of PMA cases and ranged from 53.6% to 58.6% in other studies, thus indicating that PMA is predominant in females. Our research also showed that PMA patients had less pleural invasion and were less likely to be smokers; the most common site for PMA was the lower lobe, a finding consistent with the results of previous studies …”
Section: Discussionsupporting
confidence: 92%
“…In our study, the proportion of PMA ranged from 2.92% to 4.65%, a result consistent with findings from previous studies indicating that PMA composes 2%‐10% of lung adenocarcinoma patients . Female patients accounted for the majority of PMA cases and ranged from 53.6% to 58.6% in other studies, thus indicating that PMA is predominant in females. Our research also showed that PMA patients had less pleural invasion and were less likely to be smokers; the most common site for PMA was the lower lobe, a finding consistent with the results of previous studies …”
Section: Discussionsupporting
confidence: 92%
“…I 2 and P value were used to evaluate the statistical heterogeneity. A fixed effects model was adopted with significant heterogeneity (I 2 ≤ 50% and P ≥ 0.1), while a random effects model was employed in all other instances (I 2 > 50% or P < 0.1) [22][23][24]. Risk ratio (RR) with 95% confidence interval (CI) was calculated for binary outcomes, mean difference (MD), or the standardized mean difference (SMD) with 95% CI for continuous outcomes and the hazard ratio (HR) for time-to-event outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated that CyPA and CD147 are upregulated in cancer and involved in diverse pathological processes during cancer promotion [22,23]. In the present study, we use clinical specimens and database analyses to determine the high expression levels of CyPA and CD147 in high-grade glioma.…”
Section: Discussionmentioning
confidence: 99%